The experimental and numerical study of indirect effect of a rifle bullet on the bone. (December 2015) - Zhang, Xiaoyun; Xu, Cheng; Wen, Yaoke; Luo, Shaomin
Highlights: We study the transient indirect effect of a rifle bullet on bone experimentally and computationally. We defined the bone as different layers by the gray scale to simulate its heterogeneity. The FEA model is acceptable and reasonable. The effect of different parameters on transient response of bone is also studied computationally. Abstract: We study the transient indirect effect of a rifle bullet on bone in the gelatin-bone composite target experimentally and computationally. The process of a 56 type 7.62-mm rifle bullet penetrating the composite target has been simulated using numerical method. The experiment provided the criteria for verifying the correctness of the numerical model. We have obtained tomographic data of bone by CT scans, and also defined the bone as different layers by the gray scale to simulate its heterogeneity. The computed results are in good agreement with the experimental data. Effects of the impact velocity and bone location on damage caused to the composite target have also been studied. The numerical results imply the follows: When the velocity of bullet increases, the stress on bone also increases with the earlier pressure peak; When the bone is located in a certain distance from the trajectory, it will not be fractured, although it is affected by the stress wave.